GIS tutorial for ArcGIS pro 2.8 - Gorr, Wilpen L.; aKurland, Kristen Seamens 1966-
"Learn the latest ArcGIS® Pro tools and workflows with this best-selling book! Updated for the latest version of ArcGIS Pro, GIS Tutorial for ArcGIS Pro 2.8 is the book of choice for classrooms and self-learners seeking to begin or grow their expertise using Esri's premier geographic information system (GIS) technology. This fourth edition features an updated chapter covering the newly revised geocoding workflow and tools. Students will find simplified steps and figures that match the 2.8 interface. When finished, readers will have learned how to make maps; find, create and analyze data; and manage operational systems while using ArcGIS Pro, ArcGIS Online, ArcGIS StoryMaps, ArcGIS Dashboards, ArcGIS Collector, and more. Free downloadable video lectures and lecture slides boost learning outcomes. Additional instructor resources augment instruction. Since 2005, Carnegie Mellon educators Kristen Kurland and Wil Gorr have been sharing what works in their own teaching experiences. Their other titles include, GIS Tutorial for Crime Analysis, GIS Tutorial for Health, and GIS Jumpstart for Health Professionals"--Provided by publisher.